Revision of the Rhagovelia angustipes complex (Insecta: Hemiptera: Veliidae) from Colombia - Galindo-Malagón, Ximena Alejandra; Morales, Irina; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2021)
Water striders of the genus Rhagovelia Mayr, 1865 (Insecta: Hemiptera: Veliidae) have colonized the water surface mainly in lotic freshwater systems, but also in coastal marine environments. They are characterized by the swimming fan in the distal tarsomere of the middle leg that allows them to quickly maneuver. In the Americas, it was subdivided into four monophyletic complexes (angustipes, collaris, obesa and robusta), one paraphyletic grade (abrupta), each with several groups of species, and one additional group (varipes). However, the taxonomy of this genus still has inconsistencies due to its morphological complexity and to the misinterpretation of characters. For this reason, we present a revision of the species of the angustipes complex occurring in Colombia. Material deposited in nine biological collections was examined, including several types. A total of 3,674 specimens were studied, belonging to 26 valid species, of which R. boyacensis sp. nov., R. graziae sp. nov. and R. molanoi sp. nov., are described as new; and R. angustipes Uhler, 1894 is recorded from the country for the first time. Furthermore, eleven species are redescribed and twelve are considered synonyms. Finally, a key to the species of the angustipes complex occurring in Colombia is presented, as well as updated distribution maps.